1992
DOI: 10.1080/01688639208402827
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and memory in mild senile dementia of the alzheimer type

Abstract: Glucose utilization appears to play a role in memory, and patients with Senile Dementia of the Alzheimer Type (SDAT) show particular abnormalities of the glucose system. The present study examined the effects of glucose administration on memory in subjects with mild SDAT and age-matched controls. SDAT subjects demonstrated greater overall increases in blood glucose levels following glucose administration. Normal subjects whose blood glucose levels returned to near baseline following glucose administration show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(115 citation statements)
references
References 23 publications
13
100
2
Order By: Relevance
“…Although the rationale for the therapeutic use of thiazolidinediones to compensate for hypometabolism in Alzheimer's disease has received strong support [20][21][22], the data presented here suggest that long-term administration of pioglitazone may not enhance the capacity of the brain to metabolise glucose in Alzheimer's disease. However, this may not necessarily mean that pioglitazone is deleterious to the brain.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although the rationale for the therapeutic use of thiazolidinediones to compensate for hypometabolism in Alzheimer's disease has received strong support [20][21][22], the data presented here suggest that long-term administration of pioglitazone may not enhance the capacity of the brain to metabolise glucose in Alzheimer's disease. However, this may not necessarily mean that pioglitazone is deleterious to the brain.…”
Section: Discussionmentioning
confidence: 67%
“…A growing body of evidence supports the idea that alterations in brain glucose metabolism and insulin sensitivity or signalling contribute to the pathogenesis of Alzheimer's disease. Regional decreases in the activity of glycolytic enzymes and in glucose utilisation have been detected in sporadic Alzheimer's disease [18,19], and the administration of glucose [20] or insulin [21,22] can facilitate memory in patients. This evidence has led to the notion of metabolic insufficiency or glucoregulatory impairment in Alzheimer's disease [23][24][25] and has provided a strong rationale for the therapeutic use of drugs, such as thiazolidinediones, that increase insulin sensitivity and glucose consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it was reported by Manning and colleagues (Manning et al, 1993) that the ingestion of 75 g oral glucose attenuates deficits in episodic memory performance relative to a saccharin placebo in patients with Alzheimer's disease. Craft and colleagues (Craft et al, 1992) further reported that oral glucose ingestion enhanced verbal episodic memory performance in patients suffering from Alzheimer's disease exhibiting relatively poorer glucoregulatory efficiency, but not in healthy adults of a similar age who exhibited relatively better glucoregulatory efficiency.…”
Section: Alzheimer's Diseasementioning
confidence: 98%
“…Omitting breakfast has a marked adverse effect on memory capacity (Benton & Sargent, 1992;Geisler & Polich, 1992;Benton & Parker, 1998), although results are conflicting (Craft et al, 1992). It would also appear that the quantity and quality of breakfast influences the performance of school-age children (Pollitt et al, 1982;Vaisman et al, 1996;Owens et al, 1997).…”
Section: Discussionmentioning
confidence: 99%